Double‐Crested Cormorants: Too Much of a Good Thing?. Issue 9 (12th September 2017) - Dorr, Brian S.; Fielder, David G.
Abstract : For centuries, people have viewed double‐crested cormorants Phalacrocorax auritus negatively, and human persecution coupled with environmental contamination severely reduced numbers of cormorants throughout North America. Shifts in paradigms for management of our natural resources resulted in reductions in environmental contaminants and regulatory protection of cormorants, allowing for an amazing population resurgence of this adaptable fish‐eating bird. However, for cormorants, as with some other native wildlife species the populations of which have rebounded due to conservation efforts, there have been cormorant‐societal conflicts with respect to commercial and natural resources such as aquaculture and sport fisheries. Increasing resource conflicts caused cormorants to be a priority with agencies responsible for their management, resulting in development of policy to facilitate addressing stakeholder concerns. Subsequent research and management in regard to cormorant issues have been subject to considerable challenges and debate. In this feature, we discuss the primary resource damage issues associated with cormorants, management efforts and outcomes, what we have learned, and the future with regard to cormorant management.